2011
DOI: 10.1007/s11199-011-0010-9
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Race Portrayals on Spanish-Language Television

Abstract: Gender and racial stereotypes continue to permeate our society and one context in which these stereotypes are perpetuated are the media. Although we have a history of content analysis of gender and racial portrayals on English-language television aired in the U.S., few systematic analyses have been conducted on Spanish-language television that airs in the same country. Our team of coders analyzed 466 characters and 481 2-minute intervals on 19 episodes of Spanish-language soap operas or telenovelas that aired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…The context of these representations, particularly the characterization of female characters, plays an important role in the treatment given to the construction of sexuality (Aubrey and Gamble, 2014;Eyal and Kunkel, 2008;Farrar et al, 2003;Kunkel et al, 2007;Rivadeneyra, 2011), nevertheless the setting in the past of 34 of the 84 analyzed programs does not substantially change their sexual characterization. Moreover, the central role played by infidelity in most of side storylines suggest the inextricability of sex and love relationships, emphasized by Giddens (1992Giddens ( /1993 in his seminal contribution to the subject.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The context of these representations, particularly the characterization of female characters, plays an important role in the treatment given to the construction of sexuality (Aubrey and Gamble, 2014;Eyal and Kunkel, 2008;Farrar et al, 2003;Kunkel et al, 2007;Rivadeneyra, 2011), nevertheless the setting in the past of 34 of the 84 analyzed programs does not substantially change their sexual characterization. Moreover, the central role played by infidelity in most of side storylines suggest the inextricability of sex and love relationships, emphasized by Giddens (1992Giddens ( /1993 in his seminal contribution to the subject.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the context in the analysis of the characters' sexuality has been underscored by numerous researchers inspired by the social learning theory (Eyal and Kunkel, 2008;Farrar et al, 2003;Kunkel et al, 2007;Rivadeneyra, 2011). From a feminist perspective, contextual variables are essential to correlate gender inequality with other types of social inequalities, as Gamman and Marshment (1989: 7) pointed out in the 1990's, when they criticized the depoliticization made by psychoanalytic criticism of other power relations, such as class, race and generation.…”
Section: Methodsmentioning
confidence: 99%
“…Das (2011) and Emons et al (2010), for instance, observed that men in commercials more often appear in authoritative and decision-making roles, whereas women are shown in subordinate positions. Rivadeneyra (2011), too, found that men are more likely to be shown in settings that stress values like power and money. However, evidence with regard to occupational prestige is mixed.…”
Section: Women and Ethnic Minorities In Occupational Roles On Televisionmentioning
confidence: 99%
“…This conclusion holds for various television genres, including nonfiction and fiction (most notably films, soap operas, and television commercials). Women are more likely than men to have an unknown occupational status and are more likely to be unemployed or to be portrayed in a domestic environment (Das, 2011;Glascock, 2001;Luyt, 2011;Paek, Nelson, & Vilela, 2010;Rivadeneyra, 2011;Signorielli & Bacue, 1999;Signorielli & Kahlenberg, 2001). Emons, Wester, and Scheepers (2010), for instance, concluded in their study on gender roles that Dutch television commercials construct an image in which ''he works outside the home'' while ''she drinks coffee and does the dishes'' (p. 50).…”
Section: Women and Ethnic Minorities In Occupational Roles On Televisionmentioning
confidence: 99%
See 1 more Smart Citation